Near-unisons in Afro-Cuban Ensemble Drumming - Benadon, Fernando (Empirical Musicology Review, 2017)
Working with an original corpus of Afro-Cuban drumming recordings shared by Andrew McGraw, I examine the nature and extent of non-simultaneous attacks between ensemble players. Quantitative analyses of 30,000 drum onset times in four- and five-player performances reveal that these non-simultaneities, or near-unisons, are widespread and often sizeable. Their frequency and magnitude depend on selection style, measurement method used, location of the analysis window within the bar cycle, and instruments involved. I show that near-unisons result (in part) from the layering of 'idiosyncratically' timed ostinatos, and that the effect can be achieved by layering not only different timing contours but also equivalent contours that are slightly displaced with respect to each other. I also show that near-unison configurations can be either consistent or variable, so that certain leader-follower associations remain stable from cycle to cycle while others vary more freely. Beyond pairwise associations, I explore rhythmic density via the notion of onset clusters: groups of closely spaced attacks produced by up to five different players.